Environmental hazard and health risks associated with slaughterhouses in Ibadan, Nigeria. (15th March 2021) - Dada, Olanrewaju Timothy; Odufuwa, Bashir Olufemi; Badiora, Adewumi Israel; Agbabiaka, Hafeez Idowu; Ogunseye, Nathaniel Oluwaseun; Samuel, Omoniyi Sunday
ABSTRACT: Activities in slaughterhouses result in complex multidimensional health risks and environmental pollution due to the high levels of organic waste produced that directly and indirectly can affect the health of residents living in the vicinity through the pollution of surface and underground waters as well as reduced air qualities. This research examined the environmental hazard and health risk associated with slaughterhouses in Ibadan, Nigeria. Data for the research was collected across the four seasons from 570 respondents in neighborhoods located within 300, 600 and 900 meters of the selected slaughterhouses. The research revealed a distance decay effect on the perception of the environmental hazards and health risks associated with the activities in the slaughterhouses. The research further established a statistically significant variation in health risks experienced in the different seasons of the year. The health risks experienced in the dry seasons differ significantly from the rainy seasons. The perceived environmental hazards associated with the activities of the slaughterhouses also varied across the seasons of the year. As a result of these findings it is clear that public education programmes, tighter regulation and strict enforcement should be mounted to mitigate the hazards and risks of poorly managed slaughterhouses.